Determination of Nutritional Status of Elementary School Students as a Form of Emergency Response to Natural Disasters: Penentuan Status Gizi Siswa Sekolah Dasar sebagai Bentuk Upaya Penanggulangan Darurat Bencana Alam - Fery Lusviana Widiany; Yunita Indah Prasetyaningrum; Maratusholikhah Nurtyas; Muflih; Soepri Tjahjono Moedji Widodo; Rohimah Rezia Anandari; Najwa Syazwina Aziz; Ni Wayan Ena Pratini (Altifani Journal: International Journal of Community Engagement, 2025)
One of the factors that affect student learning achievement is nutritional status. Poor nutrition that results in abnormalities in brain tissue has an impact, one of which is a decrease in cognitive function that affects student’s learning abilities. Optimal nutritional status is a benchmark for good health, so that students are expected to be fitter and more prepared for any conditions that occur, including disaster conditions. Community service activities in the form of nutritional assessments (assessment of nutritional status) of school children need to be carried out at Cancangan State Elementary School as a form of emergency response to natural disasters. The aim is to find out the nutritional status of students at Cancangan State Elementary School. The assessment of nutritional status began with anthropometric measurements, namely body weight and height, then continued with determined nutritional status using the Body Mass Index indicator according to Age (BMI/U) which was calculated using WHO-Antro software. Community service activities attended by 90 students and 11 teachers at Cancangan State Elementary School were carried out smoothly. The results of data analysis showed that there was no difference in nutritional status of BMI/A based on gender, both in students in the age group <10 years and the age group ≥10 years (p-value ≥0.05). Both female and male students were dominated by students with good (normal) nutritional status. Age and gender were not related to students' nutritional status based on BMI/A (p-value ≥0.05).